The Impact of the COVID-19 Epidemic on Risk Management Perception in Tourism Business - NINH, Nguyen Van (Journal of Environmental Management and Tourism; Vol 14 No 2 (2023): JEMT, Volume XIV, Issue 2(66), Spring 2023DO - 10.14505/jemt.v14.2(66).23, 2023)
The COVID-19 pandemic is an infectious disease; through the dispersion of steam in the air, the level of rapid global infection, normal control measures have not been effective. Scientists have access to research and publication on the impact of the COVID -19 pandemic. One of the differences in each study depends on the actual population area and habitat of each community in each country. Through this study, it will provide information on the impact relationship of the COVID-19 epidemic in the field of tourism business risk management to have a basis for understanding of tourism risk management response in sustainable tourism recovery and development. This study is based on behavioral theories, and pathogen stress theories applied extended scales to survey visitors at tourist attractions. The process of collecting data of 487 response and using structural equation modeling to analyze the data. Research results have verified the impact of the COVID-19 epidemic on risk management issues in tourism business including travel risk and management perception, risk Management places of visitors, awareness of limiting contact when traveling, hygiene and safety awareness, perceived behavioral control, emergency processing support channel. This research contributes to a better explanation of the behavioral theory framework and helps to better understand the impact of the COVID-19 epidemic in the field of tourism business risk management as well as establish emergency responses for visitors in the future.